Circulating biomarker analyses in a longitudinal cohort of patients with IPF - Ebert, Christina; Walsh, Alice M.; Sereda, Larisa; Wilson, Carole L.; Schafer, Peter H.; Fischer, Aryeh; Zhao, Lei; Ramirez-Valle, Francisco; Gordon, David; Schnapp, Lynn M. (American journal of physiology. Lung cellular and molecular physiology, 2024)
In this study, we confirmed protein expression differences in only a subset of predicted biomarkers from IPF and control subjects. Most differentially expressed proteins were predicted to be secreted from lung cells. However, a significant minority of the proteins are not known to be transcriptionally expressed by lung cells, suggesting an ongoing systemic response. The contributions of the systemic response in IPF may be important as new therapeutics are developed. Idiopathic pulmonary fibrosis (IPF) is an incurable interstitial lung disease characterized by fibrosis. Two FDA-approved drugs, pirfenidone and nintedanib, only modestly prolong survival. In this study, we asked whether levels of select circulating biomarkers in patients with IPF demonstrated changes in response to treatment over time and whether treatment with pirfenidone and nintedanib led to differential biomarker expression. Serial plasma samples from 48 patients with IPF on usual treatment and six healthy volunteers were analyzed to identify differentially expressed blood protein. Hypothesis-driven potential biomarker selection was based on recent literature, internal preclinical data, and the PROLIFIC Consortium (Schafer P. 6th Annual IPF Summit. Boston, MA, 2022) proposed biomarkers of pulmonary fibrosis. We compared our findings to public databases to provide insights into relevant signaling pathways in IPF. Of the 26 proteins measured, we found that 11 (SP-D, TIMP1, MMP7, CYFRA21-1, YKL40, CA125, sICAM, IP-10, MDC, CXCL13) were significantly elevated in patients with IPF compared with healthy volunteers but their levels did not significantly change over time. In the IPF samples, seven proteins were elevated in the treatment group compared with the no-treatment group. However, protein profiles were not distinguishable between patients on pirfenidone versus nintedanib. We demonstrated that most proteins differentially detected in our samples were predicted to be secreted from the lung epithelial or interstitial compartments. However, a significant minority of the proteins are not known to be transcriptionally expressed by lung cells, suggesting an ongoing systemic response. Understanding the contributions of the systemic response in IPF may be important as new therapeutics are developed. NEW & NOTEWORTHY In this study, we confirmed protein expression differences in only a subset of predicted biomarkers from IPF and control subjects. Most differentially expressed proteins were predicted to be secreted from lung cells. However, a significant minority of the proteins are not known to be transcriptionally expressed by lung cells, suggesting an ongoing systemic response. The contributions of the systemic response in IPF may be important as new therapeutics are developed.